Characterization of High Blended Palm Biodiesel Fuel Properties with Chemical Additive - Obed M., Ali; R., Mamat; Awad, Omar I. (Oriental Scientific Pub Co, 2015)
Palm biodiesel-diesel blended fuel feasibility at high blending ratio was investigated in this study through characterization of blend properties with additives. Diethyl ether (DEE) has been used as an oxygenated additive with the blended fuel B50 (50% biodiesel+50% diesel) at different ratios of 2%, 4%, 6% and 8%. Blended fuel properties with DEE additives were tested and evaluated according to ASTM fuel standard specifications. The results of this study is essential to qualify the trend of change of the different fuel properties with increasing additive ratio which can serve the researchers who work on biodiesel fuels to indicate the fuel suitability for diesel engine applications according to fuel standards. The results show slight improvement in density and acid value with significant decrease in viscosity by about 25% at 8% additive ratio which meets the blended fuel standard ASTM D7467. The maximum decrease in pour and cloud points are 6°C and 2°C at 8% additive ratio, accompanied by about 2.6% decrease in energy content of B50 for each 2% DEE additive ratio.